Genomic Rearrangement and Recombination of Porcine Circovirus Type 2 and Porcine Circovirus-Like Virus P1 in China - Wen, Libin; He, Kongwang (Frontiers in Veterinary Science, 2021)
Porcine circovirus type 2 (PCV2) belongs to the genus Circovirus of the family Circoviridae, and it has been associated with porcine circovirus (associated) disease (PCVD or PCVAD) in pigs. PCVAD is the generic term for a series of disease syndromes that have caused economic losses to the pig industry worldwide. Since the discovery of PCV2 in the late 1990s, the virus has continued to evolve, and novel genotypes have continued to appear. Moreover, there has been recombination between different genotypes of PCV2. This review attempts to illustrate some progress concerning PCV2 in genome rearrangement and genomic recombination with non-PCV2-related nucleic acids, particularly focusing on the porcine circovirus-like virus P1 formed by the recombination of PCV2. The presence of rearranged PCV2 genomes can be demonstrated both in vivo and in vitro, and these subviral molecules ranged from 358 bp to 1136 bp. Depending on whether it has the ability to encode a protein, the agents formed by PCV2 recombination can be divided into two categories: porcine circovirus-like viruses and porcine circovirus-like mini agents. We mainly discuss the porcine circovirus-like virus P1 regarding genomic characterisation, etiology, epidemiology, and pathogenesis. Further research needs to be conducted on the pathogenicity of other porcine circovirus-like viruses and porcine circovirus-like mini agents and the effects of their interactions with PCV2, especially for the porcine circovirus-like mini agents that do not have protein-coding functions in the genome.